2006
DOI: 10.1159/000092852
|View full text |Cite
|
Sign up to set email alerts
|

Darbepoetin alfa Administered Every Other Week Maintains Hemoglobin Levels over 52 Weeks in Patients with Chronic Kidney Disease Converting from Once-Weekly Recombinant Human Erythropoietin: Results from Simplify the Treatment of Anemia with Aranesp (STAAR)

Abstract: Background/Aim: Darbepoetin alfa, an effective treatment for anemia of chronic kidney disease (CKD), can be administered at extended intervals. Simplify the Treatment of Anemia with Aranesp® (STAAR), a multicenter, 52-week study, was conducted to assess the efficacy of darbepoetin alfa administered subcutaneously every other week (Q2W) in maintaining hemoglobin (Hb) in CKD patients not receiving dialysis. Methods: This is a subgroup analysis of subjects converted from once-weekly (QW) recombinant hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…However, although numerous reports have described q2w dosing with darbepoetin alfa, [22,26,29,30] these analyses have not focused on an elderly cohort previously naive to ESA therapy. To our knowledge, the present report is the first analysis describing the response of an elderly population to de novo q2w administration of darbepoetin alfa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although numerous reports have described q2w dosing with darbepoetin alfa, [22,26,29,30] these analyses have not focused on an elderly cohort previously naive to ESA therapy. To our knowledge, the present report is the first analysis describing the response of an elderly population to de novo q2w administration of darbepoetin alfa.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients who are naive to ESA therapy [22,26] and patients who were previously treated [29] have been shown to achieve and/or maintain target Hb levels with q2w darbepoetin alfa. Previous reports have also indicated that Hb levels in elderly subjects with CKD can be maintained with once-monthly darbepoetin alfa administration.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, third-generation EPO (CERA) requires only monthly administration and thus helps in significantly improving the quality of life. However, it has been reported to have negligible effects on morbidity or mortality like other ESAs [70]. …”
Section: Peg Therapeutics: Clinical Applications and Challenges Fomentioning
confidence: 99%
“…Darbepoetin alfa is indicated for less frequent administra- tion than the epoetins/epoetin biosimilars. Table 2a summa- rizes the evidence from clinical studies supporting the efficacy and safety of darbepoetin alfa administered once every 2 weeks (Q2W) and once every month (QM) in patients with CKD not on dialysis [21–28]. In Table 2b, studies supporting darbepoetin alfa once weekly (QW) and Q2W regimens in patients on dialysis are summarized [29–33].…”
Section: Dosing Frequencymentioning
confidence: 99%